2008
DOI: 10.4049/jimmunol.180.11.7597
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Inhibits Cysteinyl Leukotriene-Induced Activation of Human Monocytes and Monocyte-Derived Dendritic Cells

Abstract: The immunoregulatory cytokine IL-10 plays an essential role in down-modulating adaptive and innate immune responses leading to chronic inflammatory diseases. In contrast, cysteinyl leukotrienes (cysLTs), important proinflammatory mediators of cell trafficking and innate immune responses, are thought to enhance immune reactions in the pathogenesis of diseases, such as bronchial asthma, atherosclerosis, and pulmonary fibrosis. The aim of this study was to determine the IL-10 regulatory role in cysLT-induced acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
1
20
0
3
Order By: Relevance
“…IL-10, for example, down-regulated mRNA of CysLT 1 and CysLT 2 receptors in a time-and concentration-dependent fashion. In addition, cysteinyl LT-induced activation and chemotaxis of human monocytes and monocyte-derived immature DCs, measured by cytosolic Ca 2ϩ flux and immediateearly gene expression, was potently decreased by IL-10 and by the CysLT 1 antagonist MK-571 (Woszczek et al, 2008b). Of interest, maturation of DCs with LPS , a classic Toll-like receptor 4 agonist, or zymosan (Thivierge et al, 2009), a Toll-like receptor 2 agonist, down-regulated CysLT 1 R mRNA levels and protein expression and reduced functional responsiveness to LTD 4 .…”
Section: B Cyslt Receptor Expression and Immunoregulationmentioning
confidence: 99%
“…IL-10, for example, down-regulated mRNA of CysLT 1 and CysLT 2 receptors in a time-and concentration-dependent fashion. In addition, cysteinyl LT-induced activation and chemotaxis of human monocytes and monocyte-derived immature DCs, measured by cytosolic Ca 2ϩ flux and immediateearly gene expression, was potently decreased by IL-10 and by the CysLT 1 antagonist MK-571 (Woszczek et al, 2008b). Of interest, maturation of DCs with LPS , a classic Toll-like receptor 4 agonist, or zymosan (Thivierge et al, 2009), a Toll-like receptor 2 agonist, down-regulated CysLT 1 R mRNA levels and protein expression and reduced functional responsiveness to LTD 4 .…”
Section: B Cyslt Receptor Expression and Immunoregulationmentioning
confidence: 99%
“…При ремоделировании митогенез гладких мышц индуцируется факторами роста через активацию ре цепторов к ЛТ [18]. ЛТ активируют моноциты, денд ритные клетки, эозинофилы, способствуя их хемо таксису, адгезию нейтрофилов к эндотелию сосудов и продукцию IL 1 моноцитами [49,50]. ЛТ В4 синте зируется преимущественно нейтрофилами, обуслов ливает активацию и хемотаксис лейкоцитов, адге зию нейтрофилов к эндотелию и освобождение ими протеаз и супероксидных молекул [49].…”
Section: механизмы влияния ожирения на возникновение и течение баunclassified
“…При висцеральном ожире нии снижение концентрации адипонектина, в свою очередь, способствует уменьшению продукции IL 10 макрофагами [58]. IL 10, продуцируемый, главным образом, активированными Т хелперами ІІ типа и регуляторными Т клетками, угнетает функцио нальную активность макрофагов, эозинофилов, ба зофилов, тучных клеток и лимфоцитов, продукцию провоспалительных цитокинов, синтез суперокси данионов и оксида азота активированными моноци тами, хемокинов IL 8 и RANTES культурой гладких мышц бронхов и макрофагов, экспрессию CD23 + , молекул адгезии ІСАМ 1 эндотелиоцитами, регу лирует дифференцировку НК, тучных клеток, ре гуляторных Т клеток, усиливает пролиферацию В лимфоцитов и секрецию иммуноглобулинов (пре имущественно IgG, IgМ) [50].…”
Section: механизмы влияния ожирения на возникновение и течение баunclassified
“…61 During the last few years, the mechanisms and factors affecting the differentiation and maturation of DCs have been intensely studied in both in vitro and in vivo experimental settings, relevant to atherosclerosis. [128][129][130][131][132][133][134][135][136][137][138] It has been shown that Apolipoprotein A-I, the major protein component of serum high-density lipoproteins, inhibits DC differentiation and maturation. 132 PPAR-a agonists ciglitazone and fenofibrate also inhibit oxLDL-induced maturation and immune functions of DCs in vitro.…”
Section: Tissue Microenvironment In Atherosclerosis and DC Functionmentioning
confidence: 99%